2022
DOI: 10.3389/fonc.2022.821578
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tumor Immune Microenvironment and Its Associations With Molecular Characteristics in Melanoma

Abstract: BackgroundThe tumor microenvironment (TME), which involves infiltration of multiple immune cells into the tumor tissues, plays an essential role in clinical benefit to therapy. The chemokines and their receptors influence migration and functions of both tumor and immune cells. Also, molecular characteristics are associated with the efficacy of melanoma therapy. However, there lacked exploration of immune characteristics and the association with molecular characteristics.MethodsWe collected the currently availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Different approaches to melanoma subtyping were already reported [41,42], although they were generally based on genomics or cancer cell histology. Wide exploratory studies addressing the immune aspects of melanoma TME were mostly solely computational [43][44][45], yet often meticulous and conclusive. The conventional and more supervised approaches, like ours, taking advantage of publicly available transcriptomic datasets also existed [46,47]; however, they usually carried different subtype annotations for what we believe could be recognized as immune desert, excluded, and inflamed tumors based on their biological information.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches to melanoma subtyping were already reported [41,42], although they were generally based on genomics or cancer cell histology. Wide exploratory studies addressing the immune aspects of melanoma TME were mostly solely computational [43][44][45], yet often meticulous and conclusive. The conventional and more supervised approaches, like ours, taking advantage of publicly available transcriptomic datasets also existed [46,47]; however, they usually carried different subtype annotations for what we believe could be recognized as immune desert, excluded, and inflamed tumors based on their biological information.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate prediction of prognosis is pivotal for the management of ovarian cancer. CCR5 as a chemokines' receptor, which may promote invasion and metastasis [6], has been actively investigated in various cancers [7][8][9][10][11][12][13]. Although limited in the field of ovarian cancer, several studies reported that CCR5 might be associated with prognosis [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The C-C motif chemokine receptor type 5 (CCR5) is one of the G protein-coupled receptors on leukocyte surfaces and is involved in the process of host immune response, which serves as our main defense against pathogens. Emerging evidence indicates CCR5 contributes largely to the tumor invasion and metastasis [6]. High expression of CCR5 causes tumor cell migration and vascular invasion, which can result in distant metastasis of several types of tumors such as breast cancers [7][8][9], hepatocellular carcinoma [10] and prostate cancers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It encompasses the body's ability to recognize and mount a defense against cancer cells, as well as the strategies that tumors employ to evade immune surveillance. The tumor microenvironment (TME) is the area surrounding a tumor inside the body and comprising an extracellular matrix, blood vessels, fibroblasts, immune cells, inflammatory mediators, e.g., chemokines and cytokines, and others [59][60][61]. The dysregulated control of inflammation contributes to the initiation, promotion, and metastasis of cancer.…”
Section: Overview Of Tumor Immunitymentioning
confidence: 99%